(3Gdbhd GdJGe aj CMcGe GdeCehe hGdEeGes - (3CMeO Hf YeGO Hf jhSa Hf YHO GdfHj, CHh GdYHGS, TgGH GdOjf GdCbagSj Ke GdbGgQj , GHf GdpYneGO ,J (B808 (3g` s ((3eMeO Hf YHO dGdg Hf EHQGgje Gdehab s)
(3ChdgG (B:s
(3hHYO agPG eSGFd SejJgG HGdbhd GdJeGe ai CMcGe GdeCehe hGdEeGe dGjSJZfi YfgG dcKQI hbhYgG , hYehe EfJTGQgG hMUhd GdHdhi HgG s
(3BNQgG (B:s
(3hcPdc Ojf GdEadGS ef Ydjg YfO GdaGQbi fhGdgd JYGdi CYde hgPG BNQ eG jSQg Gddg GdcQje s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJH HYV GdcdeGJ HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs